Encarcerados da fé: afinidades entre a discursividade doutrinal da CCB e o “proceder” do PCC - Azevedo, Públio Carlos de (2021)
Considering the remarkable growth of the incarcerated youth population in Brazil, as shown by official figures and, concomitantly, the numerical growth of adherents to the Pentecostal evangelical faith, this Thesis aims to analyze the historical and discursive parallel between both growths in Brazil. As shown in the research, the indicated phenomenon develops in the coexistence between fields, having its apex seen in the historical cut between 1980 and 2010, as demonstrated in the official CENSUS carried out by the Brazilian Institute of Geography and Statistics (IBGE). During the development of the research, we took Max Weber as a theoretical reference, with his "elective affinity", identifying within the historical construct the intimate structure of the discursive order of both fields that generates acceptance, status of belonging within the community and sense of salvation, the Thesis proves that this order develops and sustains itself in both the Pentecostal and criminal religious fields, creating a new modality of elective affinity: the Order of Religious Discourse and the Structure of the Criminality Discourse, perceived in social relations in the free environment of peripheral communities and in the closed of detention houses. The juvenile as the central object is the point of intersection between the fields, the discussion brings the understanding that this one has in front of the dialectic between the religious doctrinal discourse and the criminal procedure, such tension is identified through the prism of the Religious Chaplain, a volunteer in religious assistance prison at Fundação Casa, SP., which through the methods of the Christian confessional chaplaincy develops weekly relationships, creates a safe and fraternal environment with delinquets of the Pentecostal evangelical faith, in compliance with socio-educational measures, excluded and unassisted by the Christian Congregation in Brazil, the CCB, one of the largest and oldest Pentecostal denominations with a historical presence in the country. As for excluded juveniles, they are accepted and sponsored by the First Command of the Capital, the PCC. Based on Michel Foucault's Order of Discourse and Hermeneutics of the Subject, the discursive influence the discussion of the problem will be investigated through the comparative method of the use of language and specific entries developed in spatial coexistence, in free transit and in the intersection between fields , and, evidenced in the new cultural habitus of the juvenile, ordering a psychosocial structure oriented by the fear of non-belonging, social exclusion and eternal damnation, concepts explained in the body of this research. As a solution proposed for the hypothesis of the problem of exclusion, abandonment, lack of assistance and hopelessness of the Pentecostal delinquent, the prison religious chaplaincy is presented, as a possible and necessary answer to the issue of abandonment